HUBUNGAN ANTARA PERHATIAN ORANGTUA DENGAN PERKEMBANGAN MORAL ANAK USIA 5-6 TAHUN DI KORONG SALISIKAN NAGARI SUNGAI BULUAH TIMUR BATANG ANAI - Indri Desvita; Ismaniar Ismaniar (Universitas Negeri Padang, 2020)
ABSTRACTThis research is motivated by the low moral development of children, this is evidenced by their behavior in everyday life and can distinguish good or bad deeds. This is thought to be caused by several factors, one of which is the lack of parental attention to children. This study aims to see a picture of parental attention, to see a picture of early childhood moral development and the relationship between parental attention and moral development of children aged 5-6 years in Korong Salisikan Nagari Sungai Buluah Timur Batang Anai. This type of research is descriptive correlational. The population in this study parents who have early childhood are 43 people. The sampling technique used simple random sampling technique as many as 35 people. The data collection technique used was a questionnaire or questionnaire, while the data analysis used the percentage formula and the product moment. The results showed that the description of parental attention to children was in the low category, the description of early childhood moral development was in the low category and there was a significant relationship between parental attention and moral development of early childhood in Korong Salisikan Nagari Sungai Buluah Timur Batang Anai.Keywords: parental attention, early childhood moral development